Artificial intelligence: Driving force in the evolution of human knowledge - Cristian Colther; Jean Pierre Doussoulin (Journal of Innovation & Knowledge (JIK), 2024)
This article proposes that artificial intelligence (AI) is positioned as a key driver of a new evolutionary stage of human knowledge, complementing human intelligence and facilitating the creation and development of sophisticated collective intelligence, defined as the noosphere, understood as the sphere of collective human thought. The study reveals several key insights into the transformative potential of AI, including its capacity to accelerate, mediate, and diffuse human knowledge. It concludes that AI not only catalyzes the existence of the noosphere but also redefines the structures and mechanisms through which human knowledge is expanded and democratized. Additionally, the document presents potential risks and significant ethical, social, and legal challenges of an AI-mediated noosphere, offering recommendations and a research agenda around the topic, and limitations and proposals for improvement to be considered in the future.
Keywords: D80; O33; O32; O39; 650; Artificial intelligence; Evolution knowledge; Noosphere; Ethical considerations; Future scenarios